Recycling Waste Plastics In Pavement Engineering: Advances, Performance Enhancement, And Circular Economy Perspectives (International Journal of Environmental Sciences, 2025)
Global accumulation of plastic waste has surpassed 400 million tons within a single year and only 9% of it is recycled which causes huge challenges to the environment and resources. One of the sustainable and scalable solutions to efficiently manage plastic waste is Avenue to Pavement. The most recent advancements and their recycling techniques are summarized in this review with special focus to aggregate, fiber, and filler usage in concrete, as well as dry and wet asphalt processes. The asphalt industry benefits from the addition of recycled plastic as it decreases the use of virgin plastics and improves the rutting resistance, fatigue life, moisture sustainability, and ageing durability. The addition of plastics to concrete lowers the density, enhances ductility, improves impact resistance and counteracts strength reduction through surface modification and hybrid composites. Recycled plastics geosynthetics, modular systems, and insulation frameworks offer long-lasting low-maintenance solutions. Issues pertaining to contamination, incompatible polymers, waste streams, microplastic emissions, and the absence of diverse regulations can be addressed through stringent feedstock requirements, advanced compatibilization, and performance-based regulations. Plastic-modified pavements can outperform the conventional systems economically and environmentally if processing is optimized and under supportive policy frameworks, according to lifecycle and economic assessments. The results generally confirm that recycled plastic integrated into pavement infrastructure is a high-performing financially feasible solution consistent with the objectives of the circular economy and global climate.